(untitled) (Eurasian Medical Research Periodical, 2022)
The aim of the study was to evaluate risk factors for the development of dyscirculatory encephalopathy in patients with type 2 diabetes mellitus. Materials and methods. 60 patients were examined, 48 women (80.0%), 12 men (20.0%) suffering from type 2 diabetes who were being treated in the endocrinology department of the 3rd TMA clinic. The age of the patients was 56.5±8.7 years, body mass index (BMI) 32.3±3.8 kg/m2, with a duration of DM 6.8± 3.7 years. Among men, 6 active smokers, with an average experience of 5.3 ± 1.1 years. The diagnosis of type 2 diabetes and the degree of compensation of carbohydrate metabolism was established according to WHO recommendations. In all patients, anthropometric parameters were evaluated with the calculation of BMI according to the Quetelet formula, blood pressure was measured for the diagnosis of hypertension, carbohydrate metabolism was studied – fasting blood glucose, postprandial glycemia and glycated hemoglobin (HbA1c). Also, total blood cholesterol was examined for the diagnosis of hypercholesterolemia. To determine the symptoms of anxiety and the degree of their severity, the Spielberger anxiety scale was used (the test is an informative way to self-assess the level of anxiety at the moment (reactive anxiety as a condition) and personal anxiety) - Spielberger State and Trait Anxiety Scale. Hemodynamics in the main arteries of the head was studied by ultrasound Dopplerography in pulsating and continuous modes. Risk factors for the development of DE were calculated according to the recommendations of L.A. Ponomareva.